A Three-Phase Current Source Inverter With Third Harmonic Injection For Grid-Connected Renewable Power Sources - Janda, Žarko S.; Ninković, Predrag; Pejović, Predrag (Proceedings, Electrical engineering institute "Nikola Tesla", 2024)
Abstract: A novel three-phase voltage-synchronized current source (VSCS) converter with third harmonic injection is proposed in this paper. Compared with the conventional vector current control (VCC), phase-locked loop (PLL) is completely removed in this method. This new type of current-source inverters is suitable for application in grid-connected renewable power sources. It is based on a three-phase six-pulse inverter topology with unidirectional switches using line-synchronous control to achieve unity displacement factor at the point of common connection. An additional power circuit to implement the third-harmonic current injection technique is used in order to improve the line current total harmonic distortion. The proposed approach ensures stable operation under weak grid condition. Experimental results on a 1.5 kW prototype with the optimal third harmonic current injection are shown. The theoretical predictions of total harmonic distortion and power factor improvement are confirmed experimentally.